2009
DOI: 10.1002/mame.200800238
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Barrier Properties of Poly(ethylene terephthalate) Nanocomposite Films

Abstract: Nanocomposites of poly(ethylene terephthalate) and two different montmorillonite‐based organoclays were prepared by a co‐rotating twin screw extruder. Dispersion of nanoclays in the polymer matrix was examined by TEM and XRD. Nanocomposites with lower content of organoclay showed exfoliated morphology while by increasing the amount of organoclay the intercalated morphology was more prevalent. Both organoclays had a good intercalation with PET and were uniformly dispersed within the polymer. Oxygen permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 14 publications
2
50
1
Order By: Relevance
“…Optimal mixing conditions and adequate surface treatment of silicates should be applied to prepare exfoliated nanocomposites [12][13][14][15][16] . The use of polymers containing polar functional groups and/or ionomers as compatibilizers also promotes the dispersion of silicates and may lead to intercalated and/or exfoliated nanocomposites [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Optimal mixing conditions and adequate surface treatment of silicates should be applied to prepare exfoliated nanocomposites [12][13][14][15][16] . The use of polymers containing polar functional groups and/or ionomers as compatibilizers also promotes the dispersion of silicates and may lead to intercalated and/or exfoliated nanocomposites [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Significant properties improvement of the polymer-matrix composites (PMCs) depends mainly on: the size and shape of nanofiller, surface area, degree of surface development, surface energy and the spatial distribution of the nanoparticles in the polymer matrix. The enhanced properties usually exhibited by such materials can significantly expand the potential applications of PET [10]. Apart from mechanical properties and processability, thermal properties and resistance to thermal degradation can be improved by the addition of appropriate nanoparticles [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…During second stage, when temperature is higher, the remaining nanotubes along with the residues of the first stage are burned. 10,20, ) methods were applied to TG data to obtain kinetic parameters (activation energy, Arrhenius constant at 600 K and A factor) and Criado method to kinetics model analysis. In this kinetic model, energy activation is increasing with the increase of nanotubes concentration.…”
mentioning
confidence: 99%
“…Nanocomposites use low filler content (usually <5%) and many studies reported poor miscibility between the organic and inorganic components, leading to agglomeration of the latter, and therefore, weaker materials at higher particle rates [6,19]. Some of the researchers determined the advantages in the mechanical, thermal or optical properties between 1-3% clay usage [3,8,10,12,20]. Therefore, in this study, the clay amount was fixed at 3%.…”
Section: Methodsmentioning
confidence: 99%
“…We set out to investigate the influence of clay type on the surface and internal structure, morphology and thermal properties of the PET-clay composite master batch. In literature, Kim [7], Litchfield et al [8], Scaffaro et al [9], Frounchi et al [10], Barber et al [11], Wang et al [12] and Solis et al [13] studied clay-PET nanocomposite production by melt intercalation method and they worked on the effect of clay amount on nanocomposite properties, particularly clay dispersion in PET polymer matrix and tensile properties. Gashti et al [14] researched the effect of clay type on dyeability of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%